Acehnese Women as Guardians of Cultural Heritage: An Analysis of Their Role in the Conservation of Arts and Traditions - Mujiburrahman, Mujiburrahman; Meliza, Richa; Riski, Aflia; Alawi, Fahrudin; Sari, Dewi Kumala (Malikussaleh Social and Political Reviews, 2024)
This article explores the central role of Acehnese women in preserving the rich and diverse traditional arts and culture. Acehnese women play a crucial role in maintaining and revitalizing various forms of cultural and artistic heritage, including traditional dance, music, literature, cuisine, religious rituals, and handicrafts. Through interviews, observations, and literature review, this research reveals how Acehnese women not only act as custodians of cultural heritage but also as innovators who adapt to changing times without abandoning their traditional roots. The article highlights the contributions of women in Acehs art and cultural communities, as well as the challenges they face in maintaining traditions amidst modernization and globalization. Thus, this article provides an in-depth understanding of the dynamics between tradition and change, and the importance of women's roles in preserving ancestral heritage for future generations.